Ultrastructural Features of an Abundant and Ubiquitous Marine Ciliate, Uronychia binucleata (Protista, Ciliophora, Euplotida) - Dong, Jingyi; Fan, Xinpeng; Zhang, Tengyue; Al-Farraj, Saleh A.; Stoeck, Thorsten; Ma, Honggang; Li, Lifang (Frontiers in Marine Science, 2020)
The ciliate genus Uronychia is a marine group with extremely differentiated cortical and ciliary structures. These structures define its unique evolutionary position in the whole subclass Euplotia. However, to date, few data about the ultrastructure of this genus and related taxa is available. In the present work, a dominant species, Uronychia binucleata, was investigated using scanning electron microscopy and transmission electron microscopy. The findings are as follows: (i) this species lacks the typical alveolar plate in its cortex, whereas the abundant electron-lucent vesicular structures occurred densely; (ii) the subpellicular microtubules form a triad configuration in the dorsal side, while appearing in a single configuration in the ventral side; (iii) the cortical granules are extrusomes, which represent a kind of mucocyst instead of ampules; (iv) two kinetosomes in different rows of one cirrus are linked by the single longitudinal connection; (v) the undulating membrane is highly developed and their insides and outsides are partially covered by the cortical flap; (vi) the single-membrane-bound pharyngeal disks interposed with microtubular sheets, and are distributed in three distinct zones. This first detailed report about the ultrastructural features of the genus Uronychia will be a key to improve the diagnosis and systematics of this widely distributed and ecologically important genus and its family Uronychiidae.